Changes in the epidemiology of hepatitis A in three socio-economic regions of China, 1990-2017 - Xiao-Jin Sun; Guo-Min Zhang; Rong-Jun Zhou; Hui Zheng; Ning Miao; Zun-Dong Yin; Fu-Zhen Wang (BMC, 2019)
Abstract Background Hepatitis A (HepA) vaccination and economic transitions can change the epidemiology of HepA. China's Gross Domestic Product (GDP) per capita was known to be inversely associated with the incidence of HepA, but a deeper understanding of the epidemiology of HepA in different socio-economic regions is lacking. We compare the changing epidemiology of HepA in three socioeconomic-geographic regions of China. Methods We obtained data on all HepA cases reported through the National Notifiable Disease Reporting System and assessed trends and changes in age-specific incidence rates by age quartile and season. We categorized the country into three regions, the sequential years into five era, compared the incidence, quartile age, seasonal intensity and coverage of HepA of the three regions. Linear regression was performed to analyse trends in incidence of HepA and to analyse the association between coverage and incidence. Results The annual mean incidences of HepA in the eastern, central, and western regions decreased from 63.52/100 000, 50.57/100 000 and 46.39/100 000 in 1990-1992 to 1.18/100 000, 1.05/100 000 and 3.14/100 000 in 2012-2017, respectively. Decreases in incidence were seen in all age groups in the three regions; the incidence was highest (9.3/100 000) in the youngest age group (0-4 years) of the western region, while in the central region, the age group with the highest incidence changed from 0 to 9 years to adults ≥60 years old. In 2017, the median age of HepA cases was 43 years (Q1-Q3: 33-55), 47 years (Q1-Q3: 32-60) and 33 years (Q1-Q3: 9-52) in the eastern, central, and western provinces, respectively. Seasonal peaks became smaller or were nearly elimination nationwide, but seasonality persisted in some provinces. After the Expanded Program on Immunization (EPI) included HepA vaccine into the routine schedule in 2007, HepA coverage increased to > 80% in the three regions and was negatively association with the HepA incidence. Conclusion The incidence of HepA decreased markedly between 1990 and 2017. A socioeconomic inequity in coverage of HepA vaccine was almost eliminated after HepA vaccine was introduced into China's EPI system, but inequity in incidence still existed in lower socio-economic developed region.